PENGARUH BUDAYA ORGANISASI, MOTIVASI KERJA, DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA KARYAWAN STUDI PADA PT. BANK JATENG CABANG KUDUS - Diego Lana Setiawan, 13.05.51.0016 (Students' Journal of Economic and Management, 2017)
The research had goals to examine and to analyse influence between organisation culture, motivation, and commitment organisational to employee performance in PT. Bank Jateng Cabang Kudus. The Sample in this research had choose 110 PT. Bank Jateng Cabang Kudus employee. Sufficiency in the amout of a sample were 100 from population who fill condition for a respondent based on Coper and Emory. In The research data Analyse technique used to double linier regression but hypotheses test used to T test and F test. The result indicated that influence positive and significant between organisation culture (X1) to employee performance (Y), The result indicated that influence positive and significant between motivation (X2) to employee performance (Y), but The result indicated that influence negative and not significant between commitment organisational (X3) to employee performance (Y). The result coefficient determination value from Adjusted R square was 0,339 or 34%. So, It was mean influence organisation culture (X1), motivation (X2), and commitment organisational (X3) in a herewith to employee performance (Y) was 34% and while 66% influence of the others variable who not included in the research.. Keyword: organisation culture, motivation, commitment organisational, employee performance.